Through animals' eyes : true stories from a wildlife sanctuary - Cuny, Lynn Marie, 1951- (University of North Texas Press, 1998)
Tells the stories of some of the animals that have been cared for at the Wildlife Rescue and Rehabilitation Sanctuary in San Antonio, Texas.